Evaluate the effect of different doses for grape seed extract in mice: Sanaa Kudair A .AL.Jeboory, Eman H.Y.Al Taae and Rajiha A. AL. Naimi - AL.Jeboory,, Sanaa Kudair A . (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study was to evaluate the effect of different doses for grape seedsextract in internal organs of mice. Histopathological, cytogentical and haematologicalstudies were done to evaluate this effect. The study was done on (24) mice divided into fourgroups (6/group) for one month. Group one treated with PBS considered as controlNegative, Group two treated with (100mg/kg B.W.) of grape seed extract, Group threetreated with (200mg/kg B.W.) of grape seed extract, Group four treated with (300mg/kgB.W.) of grape seed extract. The results showed that (200, 300mg/kg B.W.) causesignificant decrease in hematological, cytogentical parameters and severe histopathologicalchanges while at dose (100mg/kg B.W.) induce immune pathological response organ withamelioration of haematological and cytogentical parameters. In conclusion the effect ofgrape seed extract was dose dependent that more severe toxicopathological changesappeared in haemtological, cytogentical and histopathological results at doses (200 and300mg/kg B.W.) while at dose ( 100mg/kg B.W.) induce immunopathological responseinternal organs with amelioration of haematological and cytogentical parameters.